Pengaruh Love Of Money, Machiavellian, Dan Pemahaman Perpajakan Terhadap Persepsi Penggelapan Pajak (Tax Evasion) Studi Kasus Wajib Pajak Orang Pribadi Yang Terdaftar Di Kpp Pratama Surabaya Sawahan - Oky Resita Rahmania; Achmad Maqsudi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to test and analyze the effect of love of money, Machiavellian, and understanding of taxation on the perception of tax evasion on individual taxpayers registered at KPP Pratama Surabaya Sawahan. In this study using quantitative methods using primary data obtained from questionnaires. The population in this study were taxpayers registered at KPP Pratama Surabaya Sawahan. Sampling using purposive sampling technique and the sample size in this study was 100 respondents using the Slovin formula. Data analysis using SmartPLS. The results of this study indicate that love of money has a positive and significant effect on the perception of tax evasion. Meanwhile, Machiavellian and understanding of taxation have a significant negative effect on the perception of tax evasion.